A SUCCESS CASE OF WIDURI AREA REJUVENATION, ASRI BASIN, OFFSHORE SE SUMATRA BLOCK, INDONESIA - Dwandari Ralanarko; Ildrem Syafri; Abdurrokhim Almabrury; Andi Agus Nur (BULLETIN OF THE MARINE GEOLOGY, 2021)
INTA/B Field is one of the most producing mature fields in Widuri Area, Asri Basin, Offshore SE Sumatera, Indonesia, therefore it is subjected to rejuvenation to enhance hydrocarbon production. INTA/B Field is distinguished from other fields from its featured anticlinal structures that have the northeast-southwest trending. This structure is heavily faulted mainly in the up-thrown south side of a major normal fault. Two structural configurations with various oil-water contact have successfully been identified within the field. The most of oil reserves are preserved in the western lobe in which Intan-1 sands. One of the most important reservoirs in this field is Talangakar (TAF) sand deposited as a meandering river system that streamed from the northwest to the southeast within the basin. Two main reservoirs, Gita-34A and Gita-34B are correlated throughout the field and interpreted as Miocene fluvio-channel sands. These two channels are thickened moderately from southwest to northeast which has descriptions as follows: fine- to-coarse grains, unconsolidated to friable, and low cementing materials.INTA/B Field has been produced for 25 years and currently undergoing a watered-out phase. Therefore, an integrated study is subjected to overcome this issue for mature field rejuvenation. The integrated study ranged from geology (e.g., depositional environment and facies analysis), geophysics (e.g., revisiting and reprocessing of seismic attributes), petrophysical calculation, and reservoir engineering (e.g., water conformance plot and volumetric calculation).This integrated study has successfully rejuvenated a mature field resulting and added a significant number in oil production with an average of 300 BPOD/well. The extended project is estimated to have a similar result to the forward pilot.